Fracture Mechanics of Nacre‐Inspired Materials With Engineered Structural Defects - Chuang Dong (Engineering Reports, 2025)
ABSTRACT The development of high‐performance structural materials is a key challenge in materials engineering. In particular, the concurrent enhancement of strength and ductility, which are often mutually exclusive in traditional materials, remains difficult. While multi‐element composite approaches have enabled mechanical enhancement, they frequently require complex manufacturing processes. Drawing inspiration from nacre's “brick‐and‐mortar” architecture, which features a periodic arrangement of hard and soft phases, we developed a biomimetic segmented defect design strategy. This structural optimization approach facilitates the precise regulation of ductility through defect engineering rather than compositional modification. Using discrete element modeling‐based numerical simulations, we systematically examined the tensile fracture behavior of nacre‐inspired defect‐engineered structures. The data showed that controlled defect introduction enhances ductility by 30%–50% while maintaining material strength and stability. This defect design mechanism thus represents a promising approach for fabricating strong and tough engineering materials through geometry‐driven property optimization.